Library of flux-calibrated echelle spectra of southern late-type dwarfs with different activity levels - Cincunegui, Carolina Cecilia (2004)
We present Echelle spectra of 91 late-type dwarfs, of spectral types from F to M and of different levels of chromospheric activity, obtained with the 2.15 m telescope of the CASLEO Observatory located in the Argentinean Andes. Our observations range from 3890 to 6690 Å at a spectral resolution from 0.141 to 0.249 Å per pixel (R = λ/δλ ≈ 26 400). The observations were flux calibrated with the aid of long slit spectra. A version of the calibrated spectra is available via the World Wide Web†.